2023
DOI: 10.1001/jamahealthforum.2023.3648
|View full text |Cite
|
Sign up to set email alerts
|

Use of Telemedicine and Quality of Care Among Medicare Enrollees With Serious Mental Illness

Andrew D. Wilcock,
Haiden A. Huskamp,
Alisa B. Busch
et al.

Abstract: ImportanceDuring the COVID-19 pandemic, a large fraction of mental health care was provided via telemedicine. The implications of this shift in care for use of mental health service and quality of care have not been characterized.ObjectiveTo compare changes in care patterns and quality during the first year of the pandemic among Medicare beneficiaries with serious mental illness (schizophrenia or bipolar I disorder) cared for at practices with higher vs lower telemedicine use.Design, Setting, and ParticipantsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although telehealth helped preserve health care access during COVID-19, these findings suggest potential tradeoffs in quality metrics for individuals with SMI, particularly in PC engagement and continuity of care in psychotherapy or psychosocial rehabilitation settings and ICM programs. Though others report that practice-level telehealth use was associated with more visits per year for individuals with SMI [ 8 ], a subset of patients with SMI may require more robust supports (eg, from peers or case managers) to use telehealth without reducing access. Training and technical support may be necessary to overcome barriers such as hardware and software needs, broadband access, technological illiteracy, and condition-related aversions to technology mediated communication (eg, delusions) [ 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although telehealth helped preserve health care access during COVID-19, these findings suggest potential tradeoffs in quality metrics for individuals with SMI, particularly in PC engagement and continuity of care in psychotherapy or psychosocial rehabilitation settings and ICM programs. Though others report that practice-level telehealth use was associated with more visits per year for individuals with SMI [ 8 ], a subset of patients with SMI may require more robust supports (eg, from peers or case managers) to use telehealth without reducing access. Training and technical support may be necessary to overcome barriers such as hardware and software needs, broadband access, technological illiteracy, and condition-related aversions to technology mediated communication (eg, delusions) [ 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the first 6 months of the pandemic, rapid telehealth growth was associated with lower MH use among individuals with SMI [ 7 ]. A recent study of specialty mental health practices with higher telehealth use found that Medicare patients with SMI had more visits per year, but no differences in medication refills, postpsychiatric hospitalization follow-up, or all-cause mortality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%